Evaluating slow-transit constipation in patients using laxatives: a better approach or do we need improved patient selection?. (April 2012) - Bassotti, Gabrio; Villanacci, Vincenzo; Bologna, Sara
Evaluation of: Dinning PG, Hunt L, Lubowski DZ, Kalantar JS, Cook IJ, Jones MP. The impact of laxative use upon symptoms in patients with proven slow transit constipation. BMC Gastroenterol. 11, 121 (2011). Slow-transit constipation is a relatively frequent subtype of constipation, often refractory to medical treatment. Clinical information is usually obtained in patients during laxative withdrawal; thus, data on the effect of laxatives on their daily symptoms are lacking. The evaluated article reports on the effects of laxatives on symptoms (stool frequency, stool form, straining at stool, pain and bloating) and on laxative use by means of a daily stool questionnaire. Most patients used laxatives on an intermittent basis, and a minority also used associated enemas. Use of laxatives yielded an almost average normal daily number of evacuations in this group, with only a minority having less than three bowel movements per week. The days in which patients used laxatives yielded significantly more frequent and loose stools compared with those without laxatives. Thus, the use of laxatives seems to influence the clinical aspects of patients with slow-transit constipation, and this should be considered when evaluating these participants.